2018
DOI: 10.7150/ijms.27326
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid reduces indoleamine 2,3-dioxygenase 1 expression in tumor cells

Abstract: Marine plants and animals have omega-3 fatty acids including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). EPA is required for biological processes, but humans are unable to synthesize them and must be obtained from dietary sources. EPA has been used as an antitumor agent but the molecular mechanisms for the regulation of tumor microenvironment immunity by EPA are still unknown. The indoleamine 2,3-dioxygenase 1 (IDO) catalyzes conversion of tryptophan to kynurenine to induce immune evasion in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Dr. Sheu and his colleagues, the experts in the field, found that hinokitiol inhibits tumor cell migration via blocking the phosphorylation of mitogen-activated protein kinase and p65 nuclear factor kappa B (NF-κB) [15]. Our findings verified that the expression of phosphorylated Akt/Erk is decreased in hinokitiol-treated B16F10 and 4T1 tumor cells, which is consistent with the results published by other groups [15][16][17][18][19]. We also used resveratrol and constitutively active Akt transfection to make a thorough inquiry on the association of heparanase and these two pathways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dr. Sheu and his colleagues, the experts in the field, found that hinokitiol inhibits tumor cell migration via blocking the phosphorylation of mitogen-activated protein kinase and p65 nuclear factor kappa B (NF-κB) [15]. Our findings verified that the expression of phosphorylated Akt/Erk is decreased in hinokitiol-treated B16F10 and 4T1 tumor cells, which is consistent with the results published by other groups [15][16][17][18][19]. We also used resveratrol and constitutively active Akt transfection to make a thorough inquiry on the association of heparanase and these two pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Murine melanoma cells (B16F10) [16] and murine mammary carcinoma (4T1) cells [17] were maintained in 10cm culture dish with Dulbecco's Modified Eagle Medium (DMEM) containing 1% Penicillin-Streptomycin (100 units/mL penicillin and 100 μg/mL streptomycin), and 10% fetal bovine serum (FBS). Both B16F10 and 4T1 cells were incubated at 37°C, 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…EPA modulated in immunity and inhibits the expression of intracellular interleukin-2, tumor necrosis factor -α, and interleukin-4 in T cells 9. Previously, we found that EPA did not influence the proliferation of T cells 8. Meanwhile, EPA reduced the function of antigen-presenting cells 10, 11.…”
Section: Introductionmentioning
confidence: 87%
“…Humans obtain these from dietary sources, because humans are not able to synthesize EPA 7. EPA has anti-inflammatory and antitumor abilities that work by regulating cellular signal pathways 8. EPA modulated in immunity and inhibits the expression of intracellular interleukin-2, tumor necrosis factor -α, and interleukin-4 in T cells 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation